MEDICINAL BIOMAGNETISM IN IMPROVING THE QUALITY OF LIFE - SELF-CARE PROTOCOL - Teresa Spaniol Pelissari, Rosani; Viapiana Bossa, Adriane (Health and Society, 2023)
Medicinal Biomagnetism (BM) is a natural, non-invasive and painless therapeutic system that has been in development for over 30 years. It presents itself as an Integrative and Complementary Practice (PIC). It works in the prevention, diagnosis and treatment of bioelectrical and biomagnetic dysfunctions, aiming at the energy rebalance of living beings as a whole, contributing to the treatment of diseases. Homeostasis is a foundation of BM whose principle is the balance that goes beyond the organic integrative physiological state. Energetic, emotional, dysfunctional, psycho-emotional, spiritual aspects, Chakras among others are considered. The state of equilibrium is called Normal Energy Level (NEN) and it measures the health or illness of the individual. The treatment of bioelectromagnetic dysfunctions takes place through static magnetic fields generated by magnets specific to the technique. In the last decade, several protocols have been developed that aim to balance the body’s energy imbalances. The objective of this work is to present the BM therapeutic system and a self-care protocol for the balance of energy absorption and distribution centers for the body, called Chakras, aiming at improving the quality of life. A descriptive bibliographic review of a qualitative nature and exploratory nature of the themes related to the theme was used as a method of study. As a result, we have the presentation of the BM and the Chakras/Gland Protocol that can be used by health professionals, therapists or people who strive for self-responsibility in care, disease prevention, improvement in the quality of vital energy and quality of life. We conclude that it is important to continue producing scientific evidence related to BM, without leaving aside the principles of PICs to simply stimulate self-care and self-management of quality of life.